Transcultural adaptation and reliability of the Spanish version of a questionnaire about oral hygiene advice given by dentists in Chile. - Ilze Maldupa; Jaime Aguila; Pablo Toloza; Sergio Uribe (Universidad de Concepción., 2015)
Aim: To adapt and evaluate validity and reliability of the Spanish version of a questionnaire about oral hygiene advice given by dentists in Chile Materials and methods: A validation study was conducted according to recommendations of COSMIN. The original questionnaire was adapted from English into Spanish using translation, back translation, expert review and pilot test sample by 56 dentists. The instrument consisted of 3 sections: recommendations for oral hygiene, relevance given to delivery of oral hygiene instruction and training and experience in delivering oral hygiene recommendations. It was reapplied in 5 of them a week later. Reliability was measured with internal consistency (Cronbach's alpha), test-retest reliability (Cohen's kappa and weighted kappa) and measurement error (limits of agreement, LdA). Content validity was evaluated by experts and construct validity by using convergent validity (Pearson correlation). Results: A good level of internal consistency that applies to 5 items (Cronbach's alpha=0.73) was obtained. For items on a nominal scale, Cohen Kappa coefficient was 0.80 (95% CI=0.64 to 0.95) and for ordinal items weighted kappa coefficient (linear weighting) was 0.76 (95% CI=0.65 to 0.88). The difference between the scores calculated for the measurements was 1 standard deviation 2.35. Ninety five percent of the differences were between -5.7 to 3.7 (+/-4.7 LoA=1) and the variance of the total score was 29- 41. A good level of convergent validity (Pearson correlation=0.63) was obtained. Conclusion: The final questionnaire is valid and reliable to be applied to Chilean dentists with a profile like those included in this study in order to identify and quantify the oral hygiene instruction they provide to patients. Future studies should assess validity and reliability of this adaptation for other Spanish-speaking countries.